PENGARUH STRUKTUR KEPEMILIKAN, LEVERAGE, PROFITABILITAS DAN KEBIJAKAN DIVIDEN TERHADAP MANAJEMEN LABA DENGAN KUALITAS AUDIT SEBAGAI VARIABEL MODERASI - Ayu Dwi Hasty; Vinola Herawaty (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2017)
This study aims to examine the effect of ownership structure, leverage, profitability and dividend policy on earnings management. In addition, this study wanted to test audit quality as a moderating variable on the relationship between ownership structure, leverage, profitability and dividend policy on earnings management. Independent variables used in this research are managerial ownership, leverage, profitability, and dividend policy. Dependent variable used in this research is earnings management. While the moderation variable used in this research is audit quality. The sample in this research is a manufacturing company listed on Indonesia Stock Exchange in the period 2013-2015. The total sample used was 99 for three consecutive years, taken through purposive sampling. The method of analysis of this research using multiple linear regression analysis. The results of this study indicate that managerial ownership negatively affect earnings management, leverage and profitability have a positive effect on earnings management, while dividend policy has no positive effect on earnings management for model 1. As for model 2 shows that managerial ownership has a significant negative effect on earnings management, leverage, profitability and dividend policy have a positive effect on earnings management. Audit quality is not able to moderate the relationship between managerial ownership, leverage, profitability, dividend policy on earnings management.Keywords: managerial ownership, leverage, profitability, dividend policy, earnings management, audit quality